Efektivitas Bimbingan Kelompok Dengan Teknik Rational Emotive Behavior Therapy (Rebt) Untuk Meningkatkan Kedisiplinan Melaksanakan Ibadah Sholat Pada Mahasiswa Semester Akhir: Penelitian - Jannati, Zhila; Putra, Bela Janare; Sunaryo, Ajimas Aziz (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the effectiveness of group guidance using the Rational Emotive Behavior Therapy (REBT) technique in improving the discipline of performing prayers among final semester students in the Islamic Guidance and Counseling Study Program at UIN Raden Fatah Palembang. The background of this study is based on the phenomenon of low student discipline in performing prayers due to academic pressure, poor time management, and irrational thought patterns that hinder consistent worship. This research employs a quantitative approach with an experimental method. The sample consisted of 10 students selected through purposive sampling based on pretest results indicating a low level of discipline. The research instrument was a prayer discipline questionnaire, and data analysis was conducted using the Paired Sample T-Test through SPSS version 26. The results showed a significant increase between pretest and posttest scores, with the mean score rising from 67 to 102. The significance value (Sig. 2-tailed) of 0.000 < 0.05 indicates a significant difference before and after the treatment. This proves that group guidance using the REBT technique is effective in improving the discipline of performing prayers. Through this guidance activity, students were able to recognize irrational thoughts, transform them into rational ones, and foster spiritual motivation and responsibility to worship on time and consistently. This study is expected to serve as a reference for educational institutions in developing guidance services based on psychological and spiritual approaches.